Cementoin-SLPI fusion protein binds to human monocytes and epithelial cells and shows higher biological activity than SLPI - Maffia, Paulo Cesar (2018)
Secretory Leukocyte Proteinase Inhibitor (SLPI) is an antiinflammatory peptide that blocks the activity of serine proteases, primarily the neutrophil elastase. In an attempt to direct the activity of SLPI on inflamed sites, a chimera consisting of the transglutaminase II substrate domain of trappin 2 (cementoin), and the mature SLPI protein was constructed. Cell attachment and biological activity were compared between SLPI and this chimera. By using whole cell ELISA, fluorescence microscopy and flow cytometry assays we observed that the cementoin-SLPI fusion protein (FP) but not SLPI attached to a human lung epithelial cell line and monocytes. A maximum attachment was achieved 15 min after FP was added to the cell cultures. In an elastase activity assay, we observed that FP retained its antiprotease activity and that at equimolar amount of proteins, FP was more efficient than SLPI in the inhibition. Both, FP and SLPI inhibits IL-2-induced lymphocyte proliferation, however, lower amounts of FP were required to achieve this inhibition. Furthermore, FP binds to mycobacteria and maintained the bactericidal activity observed for SLPI. Overall, these results show that this new chimera is able to attach to the cell surfaces retaining and improving some biological activities described for SLPI.